Photosynthetic responses to drought stress in different Aegilops species - Molnár, István (Acta Biologica Szegediensis, 2005)
The effects of drought stress induced by withholding water in soil pot were investigated on processes related to CO2 fixation of wheat, Ae. tauschii, Ae. speltoides and Ae. bicornis genotypes. A decrease in relative water content (RWC) of leaves from 95% to 85% resulted in intense stomatal closure and significant decrease in the net CO2 fixation in wheat and Ae. bicornis genotypes, while in Ae. tauschii and Ae. speltoides genotypes, gs and A parameters remained significantly high between 90% and 70% RWC. Despite the intense stomatal closure, the mesophyll limitation (Lm) to A, calculated from the A/Ci curves, dominated in wheat and Ae. bicornis genotypes, while the stomatal limitation (Ls) were typical of Ae. tauschii and Ae. speltoides genotypes during drought stress. These properties of Ae. tauschii and Ae. speltoides genotypes could be suitable for improving drought tolerance of wheat through intergeneric crossing.